Description of Aphelenchoides macrospica n. sp. (Nematoda Aphelenchoididae) from Northwestern Iran - Golhasan, Behrouz (Journal of nematology, 2017)
Aphelenchoides macrospica n. sp. is described and illustrated from the West Azerbayjan province, northwestern Iran. The new species is characterized by its body length of 807 to 963 μm (males) and 792 to 1,094 μm (females), offset cephalic region, lateral fields with four incisures, long stylet with 15 to 16 μm length, and excretory pore situated opposite or behind the nerve ring. Pharyngeal glands overlapping intestine dorsally and extending for 90 to 121 μm, tail terminus mucronate in both sexes. Vagina directed anteriad, and spicules are relatively large (27-32 μm) with well-developed broadly rounded apex and condylus. The new species comes close to seven known species of the genus namely A. arcticus, A. blastophthorus, A. haguei, A. huntensis, A. lucknowensis, A. parasaprophilus, and A. xui, but it differs from them by the body size, stylet length, size of spicules, and length of postvulval uterine sac. The results of phylogenetic analyses based on sequences of D2-D3 expansion region of 28S and 18S rDNA, confirmed its status as a new species